1946
DOI: 10.1002/cne.900840303
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the ventral external arcuate fibers and their continuity with the striae medullares of the fourth ventricle of man

Abstract: ) on the course of the medullary striae of Piccolomini of the fourth ventricle (long known as striae medullares acusticae) of the human brain, in which emphasis is placed on their cerebellar relations, brings up again their probable continuity with the ventral external (crossed) arcuate fibers and hence the origin and course of the latter. Apparent continuity of the ventral external arcuate fibers with the medullary striae, via fibers in the raphe, has been noted repeatedly, especially since the advent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1948
1948
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…It also had been recognized, however, that the rhombic lip is the origin of neurons not only of the basis pontis, but also the ION and AN (Essick, 1912;Rodriguez and Dymecki, 2000;Gilthorpe et al, 2002), that the AN and ION neurons begin migration prior to the pontine neurons, and that the neurons of the AN may bear a closer relationship to the ION neurons. Both ION and AN neurons migrate over the lateral and ventral surface of the medulla in a path that resembles the AEAF (Essick, 1912;Rasmussen and Peyton, 1946;Filiano and Kinney, 1992). Immunohistochemical analysis also has been used to study the origin of the AN in the FIGURE 7 | Axonal density in the medullary pyramid (left panel) and the AEAF (right panel).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also had been recognized, however, that the rhombic lip is the origin of neurons not only of the basis pontis, but also the ION and AN (Essick, 1912;Rodriguez and Dymecki, 2000;Gilthorpe et al, 2002), that the AN and ION neurons begin migration prior to the pontine neurons, and that the neurons of the AN may bear a closer relationship to the ION neurons. Both ION and AN neurons migrate over the lateral and ventral surface of the medulla in a path that resembles the AEAF (Essick, 1912;Rasmussen and Peyton, 1946;Filiano and Kinney, 1992). Immunohistochemical analysis also has been used to study the origin of the AN in the FIGURE 7 | Axonal density in the medullary pyramid (left panel) and the AEAF (right panel).…”
Section: Discussionmentioning
confidence: 99%
“…There are two main projection pathways for axons from the AN. Some axons from the AN project anteriorly onto the ventral surface of the medulla in the anterior external arcuate fasciculus (AEAF), which traverses the inferior olive as a circumolivary bundle and ultimately projects to the cerebellum via the inferior cerebellar peduncle; others project posteriorly into the medullary reticular formation (Rasmussen and Peyton, 1946;Zec et al, 1997;Fu and Watson, 2012). In the mouse, the cerebellar target of the AN-like structure is the paraflocculus of the contralateral cerebellar cortex (Fu and Watson, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, this nucleus has been considered a relay nucleus from the cerebral cortex to the cerebellum via the external arcuate fibers and inferior cerebellar peduncle. 44 In a comparative anatomic study between the human infant and cat VMS, we found that the arcuate nucleus, nucleus conterminalis, and foci of thickened marginal glia in the human are anatomically homologous to the cat RCFs. 45 This homology is based on cytoarchitectonic criteria (including cell size, shape, and distance from the surface), as defined in the combined neuroanatomic and physiologic studies of the cat RCFs of Trouth et al, 41 Schläfke et al, 35 and others [37][38][39][40][41][42][43] , and on three-dimensional cell distributions, as determined with the aid of computer reconstructions.…”
Section: Filiano MD 2 and Wf White Mdmentioning
confidence: 83%
“…Classically, the Arc is considered a precerebellar relay nucleus, similar to the pontine nuclei, with input from the cerebral cortex and projections to the cerebellum via the inferior cerebellar peduncle (Olszewski and Baxter 1982;Rasmussen and Peyton 1946). A totally different view of the Arc has been proposed on the basis of neuropathological observations showing aplasia of the Arc in the brains of children who died of SIDS (Sudden Infant Death Syndrome).…”
Section: Introductionmentioning
confidence: 99%